Evaluating the Effectiveness of Online Peer Assessment Frameworks for Group-Based Assessment in Higher Institutions of Learning - Kalema, Job; Katusiime, Jane; Kawuma, Simon; Natumanya, Deborah (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2025)
This study assesses the effectiveness of online peer assessment frameworks in higher institutions of learning through a quantitative analysis. The research explores the relationships between several dimensions of online peer assessment, comprising participant engagement, perceived challenges, and the effectiveness of online collaborative tools. Employing a sample of 154 participants, data were collected via surveys, and statistical methods, including factor analysis, t-tests, and regression analysis, were applied to examine the results. The findings indicate a generally positive perception of online peer assessment, with significant correlations between technical support and user satisfaction. The effects of these results highlight the need for higher institutions of learning to address technical challenges and improve support mechanisms to improve the effectiveness of online peer assessment frameworks.